THE EFFECT OF CAPITAL STRUCTURE, COMPANY SIZE, INTEREST RATE, PROFITABILITY AND REVENUE GROWTH ON STOCK PRICES (Case Study on Transportation Companies in the Air, Land and Sea Transportation Sub-Sector Listed on the IDX) - M Albani; Chairil Akhyar; Marzuki; Zulfan (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to analyze the effect of capital structure, firm size, interest rates, profitability, and revenue growth on stock prices of transportation companies in the air, land, and sea transportation sub-sectors listed on the Indonesia Stock Exchange during the 2019–2023 period. The research data were obtained from the official website www.idx.co.id. This study employed a purposive sampling technique, resulting in a sample of 16 companies with a total of 80 observational data points. The data were analyzed using the Panel Data Regression method with the aid of EViews 12 software, employing the Random Effect Model. The results of the study show that capital structure (DER) has a positive and significant effect on stock prices. Firm size has a positive but not significant effect on stock prices. Interest rates (BI Rate) have a positive but not significant effect on stock prices. Profitability (ROA) has a positive but not significant effect on stock prices. Revenue growth (Rev Growth) has a positive and significant effect on stock prices. Simultaneously, capital structure (DER), firm size, interest rates (BI Rate), profitability (ROA), and revenue growth (Rev Growth) collectively have a positive and significant effect on stock prices.